QTL mapping and transcriptomic analysis of fruit length in cucumber - Xing, Yanan; Cao, Yilin; Ma, Yanan; Wang, Fu; Xin, Shijie; Zhu, Wenying (Frontiers in Plant Science, 2023)
A total of 151 recombinant inbred lines (RILs) were derived from the cross between 'PI183967'(Cucumis sativus L. hardwickii) (HW) and a cultivated Northern Chinese inbred line, 'XinTaiMiCi' (XTMC). A genetic map containing 600 bin markers was constructed via re-sequencing. Based on the phenotype data collected in two different seasons (spring 2021 and autumn 2022), the major quantitative trait loci (QTLs) controlling cucumber fruit length were located and their transcriptomic analysis carried out. The results revealed three QTLs (Fl2.1, Fl4.1, and Fl6.1) detected repeatedly in the two seasons, of which Fl4.1 was the dominant QTL. From the functional annotation of corresponding genes there, we discovered the gene Csa4G337340 encoding an auxin efflux carrier family protein. The expression of that gene was significantly lower in XTMC and the long-fruit RIL lines than in HW and the short-fruit RIL lines; hence, we speculated the gene could be negatively correlated with the fruit length of cucumber. Transcriptomic analysis showed that 259 differentially expressed genes (DEGs) were enriched in the plant hormone signal transduction pathway. In addition, among those DEGs, 509 transcription factors were detected, these distributed in several transcription factor gene families, such as bHLH, AP2/ErF -ERF, C2H2, and NAC. Therefore, we concluded that the major gene controlling the fruit length of cucumber is located in the interval of Fl4.1, whose gene Csa4G337340 may be involved in the negative regulation of fruit length. Further, genes related to plant hormone signal transduction and several transcription factors were also found involved in the regulation of cucumber fruit length. Our results provide a reference for the fine mapping of major genes and analyzing the mechanism of cucumber fruit length.